Activation in Visual Cortex Correlates with the Awareness of Stereoscopic Depth - Brouwer, Gijs Joost (J Neurosci, 2005)
Using event-related functional magnetic resonance imaging, we studied the activation correlating with the awareness of stereoscopic depth using a bistable slanted surface (slant rivalry). Bistability resulted from incongruence between two slant-defining cues: binocular disparity and monocular perspective. The stimulus was perceived as alternating between the perspective-dominated percept (monocular depth) and the disparity-dominated percept (stereopsis), while sensory input remained constant, enabling us to study changes in awareness of depth associated with either cue. Transient activation relating to perceptual alternations was found bilaterally in the caudal part of the intraparietal sulcus, in the right-hemispheric anterior intraparietal sulcus, within visual area V4d-topo, and inferior to area MT+. Transient activation correlating specifically with alternations toward the disparity-dominated percept was found in a number of visual areas, including dorsal visual areas V3A, V7, and V4d-topo and visual areas MT+ and lateral occipital complex. No activation was found for alternations toward the perspective-dominated percept. Our results show that of all visual areas responsive to disparity-defined depth, V4d-topo shows the most robust signal changes correlating with the instigation of stereoscopic depth awareness (stereopsis).